Survei Kemampuan Gerak Dasar Siswa Kelas Atas di SD Negeri 2 Bojasari Kecamatan Kertek Kabupaten Wonosobo - Maharani, Anggita Putri; Raharjo, Hermawan Pamot (Indonesian Journal for Physical Education and Sport, 2023)
There was a decrease in the level of student activity in carrying out basic movement skills caused by post-pademic online learning. The purpose of this study was to determine the basic movement abilities of upper grade students at SD Negeri 2 Bojasari. This study uses a quantitative descriptive method with a percentage. The population in this study were all upper class students at SD Negeri 2 Bojasari, totaling 80 students. The sampling technique uses total sampling. The research instrument uses a motor ability test. The results of the research on the basic movement abilities of fourth grade students at SD Negeri 2 Bojasari 3.03% (1 student) Very high, 27.27% (9 students) High, 33.33% (11 students) moderate, 33.33% (11 students) ) Low, and 3.03% (1 student) very low. Basic motor skills of fifth grade students of SD Negeri 2 Bojasari, 3.70% (1 student) Very high, 11.11% (3 students) High, 51.85% (14 students) moderate, 18.52% (5 students) Low, and 14.81% (4 students) Very Low. Basic motor skills of class VI SD Negeri 2 Bojasari, amounting to 10.00% (2 students) Very high, 40.00% (8 students) High, 25.00% (5 students) Moderate, 25.00% (5 students ) Low, and 0% (0 students) Very Low. The conclusion from this study was that the basic movement ability level of fourth grade students.